Catalytic Aerobic Oxidation of C(sp3)−H Bonds. Issue 24 (8th April 2019) - Sterckx, Hans; Morel, Bénédicte; Maes, Bert U. W.
Abstract: Oxidation reactions are a key technology to transform hydrocarbons from petroleum feedstock into chemicals of a higher oxidation state, allowing further chemical transformations. These bulk‐scale oxidation processes usually employ molecular oxygen as the terminal oxidant as at this scale it is typically the only economically viable oxidant. The produced commodity chemicals possess limited functionality and usually show a high degree of symmetry thereby avoiding selectivity issues. In sharp contrast, in the production of fine chemicals preference is still given to classical oxidants. Considering the strive for greener production processes, the use of O2, the most abundant and greenest oxidant, is a logical choice. Given the rich functionality and complexity of fine chemicals, achieving regio/chemoselectivity is a major challenge. This review presents an overview of the most important catalytic systems recently described for aerobic oxidation, and the current insight in their reaction mechanism. Abstract : Oxidation reactions are a key technology to transform petroleum feedstock into chemicals of a higher oxidation state. Considering the strive for greener production processes the use of O2, the most abundant and greenest oxidant, is a logical though not self‐evident choice in the fine chemicals industry. This Review presents an overview of the most important catalytic systems recently described for aerobic C(sp 3 )−H oxidation, and the current insight in their reaction mechanism.